Losing the car keys: wireless PHY-layer insecurity in EV charging - Baker, R; Martinovic, I (USENIX, 2019)
Electric vehicles (EVs) are proliferating quickly, along with the charging infrastructure for them. A new generation of charger technologies is emerging, handling more sensitive data and undertaking more complex interactions, while using the charging cable as the communication channel. This channel is used not only for charging control, but will soon handle billing, vehicle-to-grid operation, internet access and provide a platform for third-party apps — all with a public interface to the world. We highlight the threat posed by wireless attacks on the physical-layer of the Combined Charging System (CCS), a major standard for EV charging that is deployed in many thousands of locations worldwide and used by seven of the ten largest auto manufacturers globally. We show that design choices in the use of power-line communication (PLC) make the system particularly prone to popular electromagnetic side-channel attacks. We implement the first wireless eavesdropping tool for PLC networks and use it to observe the ISO 15118 network implementation underlying CCS, in a measurement campaign of 54 real charging sessions, using modern electric vehicles and state-of-the-art CCS chargers. We find that the unintentional wireless channel is sufficient to recover messages in the vast majority of cases, with traffic intercepted from an adjacent parking bay showing 91.8% of messages validating their CRC32 checksum. By examining the recovered traffic, we further find a host of privacy and security issues in existing charging infrastructure including plaintext MAC-layer traffic recovery, widespread absence of TLS in public locations and leakage of private information, including long-term unique identifiers. Of particular concern, elements of the recovered data are being used to authorise billing in existing charging implementations. We discuss the implications of pervasive susceptibility to known electromagnetic eavesdropping techniques, extract lessons learnt for future development and propose specific improvements to mitigate the problems in existing chargers.